2013
DOI: 10.1007/s11060-013-1239-7
|View full text |Cite
|
Sign up to set email alerts
|

Atypical and malignant meningioma: outcome and prognostic factors in 68 irradiated patients

Abstract: Meningiomas account for up to 20 % of all primary intracranial neoplasms; although the majority of these have a benign course, as many as 5-10 % can display more aggressive behavior and a higher incidence of disease progression. The benefit of immediate adjuvant radiotherapy is still being debated for atypical and malignant meningiomas. This study aimed to retrospectively assess prognostic factors and outcome in 68 patients with atypical and malignant meningiomas. Sixty-eight meningioma patients were treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
20
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 22 publications
6
20
0
1
Order By: Relevance
“…Detti et al found size to have a significant impact on recurrence at 5 cm, which is similar to the value used in our study 17 . A study by Pizem et al provides a possible explanation for this association, by identifying both size and grade as predictors of brain invasion 18 .…”
Section: Discussionsupporting
confidence: 88%
“…Detti et al found size to have a significant impact on recurrence at 5 cm, which is similar to the value used in our study 17 . A study by Pizem et al provides a possible explanation for this association, by identifying both size and grade as predictors of brain invasion 18 .…”
Section: Discussionsupporting
confidence: 88%
“…A retrospective case series supports the observation that postoperative radiotherapy may result in lower rates of recurrence of atypical meningiomas that have undergone initial gross total resection: actuarial recurrence rates within 5 years were close to 42% without radiotherapy and 20% with radiotherapy 27. In the current study, age and radiotherapy dosage were associated with longer 5- and 10-year actuarial overall survival rates, while size and grading of the tumor influenced the 5- and 10-year disease-free survival rates 28. In the present case, after the patient was diagnosed with meningioma, he received surgical intervention and participated in radiotherapy for the residual tumor.…”
Section: Discussionsupporting
confidence: 86%
“…Detti et al found size to have a significant impact on recurrence at 5 cm, which is similar to the value used in our study. 17 A study by Pizem et al provides a possible explanation for this association, by identifying both size and grade as predictors of brain invasion. 18 Brain invasion has been demonstrated to have a powerful impact on recurrence and has been thoroughly reviewed by Modha et al 10 These studies together provide both support for our findings and rationale for the use of adjuvant RT in larger tumors, even when GTR is obtained.…”
Section: Discussionmentioning
confidence: 99%